(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Sorghum (Sorghum bicolor L. Moench) is a vital cereal crop cultivated in various parts of the world due to its adaptability to different climatic conditions and its importance as a food and fodder crop. The growth and development of sorghum, like other crops, is significantly influenced by its leaf area, which is a critical factor in determining the photosynthetic capacity and overall productivity of the plant. This article explores the changes in leaf area during different vegetative stages of sorghum, focusing on two varieties: Sorghum durra (Forsk) Stapf and Sorghum vulgare (L.) Moench, under varying nitrogen levels [1].